A specific character of functioning of odourative vocabulary in M. Kotsyubynsky’s works (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
Vocabulary of perception is constantly attracting researchers’ attention. The article deals with the odourative vocabulary in M. Kotsyubynsky’s works. The author investigates appropriate thematic groups of lexemes with semantics of «odour».
Keywords: vocabulary of perception; thematic groups; odour; odourative vocabulary